Acute shortening and subsequent lengthening of the radius and ulna for the treatment of an infected nonunion in a dog - Rahal, Sheila Canevese [UNESP]; Volpi, R. S.; Vulcano, Luiz Carlos [UNESP]; Ciani, R. B. (Canadian Vet Med Assoc, 2001)
A 3-year-old, male crossbred dog with osteomyelitis of the radius and ulna was treated using Ilizarov's method. Two centimeters of infected bone was resected, then acute bone shortening and subsequent lengthening of a healthy bone site were performed. The infection was eradicated, but a residual leg-length discrepancy was present.